Medical Product Sales Forecasting for Business Optimization Using Double Exponential Smoothing - Salsa Fitiansyah; Sumijan; Devia Kartika (PT. Teknologi Futuristik Indonesia, 2025)
Accurate sales forecasting plays a critical role in inventory management, particularly for medical equipment companies where stock availability directly affects operational efficiency and customer service. However, many small and medium-scale distributors still lack reliable forecasting systems, resulting in overstocking, high storage costs, or stockouts that lead to missed sales opportunities. Addressing this gap, this study aims to develop a web-based sales prediction system for PT Etiqa Prima Utama—a medical equipment distributor in Padang, West Sumatra—by applying the Double Exponential Smoothing method. The system was designed using PHP and MySQL to generate monthly sales forecasts for various medical products based on historical data. Key findings show diverse forecast accuracy across 20 product categories. The Glucose HK product achieved the lowest MAPE value at 10%, indicating excellent predictive performance, while the Clean Chem product showed the highest MAPE at 54%. Several other products, such as Total Bilirubin (12%), Urea (10%), and Diluent 20L (14%), demonstrated favorable accuracy with MAPE values below 60%. These results imply that Double Exponential Smoothing can support inventory optimization by providing reasonably accurate forecasts for most products, enabling better stock planning and more informed decision-making within the company.